INFLUENCE OF PHOTOSTIMULATION ON THE FUNCTIONAL STATE OF THE HUMAN BRAIN - BEREZOVCHUK, L.; MAKARCHUK, N. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
The study found that during the test with photostimulation, both in the presence of the phenomenon of reproduction of the rhythm of light flicker, and in its absence, the brain shows a pronounced reaction, as evidenced by significant changes in total bioelectric signal power in the cerebral hemispheres (CH). In the absence of the reaction of assimilation of the rhythm of light flicker in the subjects in most cases there is a decrease in the total signal strength in the CH. In the presence of a reaction of assimilation of the rhythm of light flicker, when the EEG visually observes oscillations that coincide with the frequency of the stimulus, the total signal strength in the hemispheres can both increase and decrease. At the same time, the largest increase in signal strength of individual rhythms during photostimulation is not always observed at the stimulation frequency. The results of the study suggest that the phenomenon of brain reproduction of the rhythm of light flicker observed on the EEG during photostimulation, and a decrease or increase in the total power of the bioelectric signal in the CH, are different physiological phenomena. This may mean that the absence of a response to the assimilation of the rhythm of light flicker during photostimulation is a more physiological response of the brain to the stimulus than the presence of such a reaction. This conclusion gives reason to believe that the presence of assimilation of the rhythm of light flicker at any of the frequencies during the test with photostimulation, and even more so, the presence of the 2nd and 3rd harmonics, is a manifestation of brain pathology. This approach to the evaluation of the sample with photostimulation correlates with the results of the test "with the eye open", which is also used to determine the reactivity of the human brain by exposure to the visual analyzer.
Keywords: electroencephalogram, photostimulation, total capacity of bioelectrical signal